Improving Workplace Climate in Large Corporations: A Clustered Randomized Intervention - Sule Alan; Gozde Corekcioglu; Matthias Sutter (Center for Economic Studies and ifo Institute (CESifo), 2021)
We evaluate the impact of a program aiming at improving the workplace climate in corporations. The program is implemented via a clustered randomized design and evaluated with respect to the prevalence of support networks, antisocial behavior, perceived relational atmosphere, and turnover rate. We find that professionals in treated corporations are less inclined to engage in toxic competition, exhibit higher reciprocity toward each other, report higher workplace satisfaction and a more collegial atmosphere. Treated firms have fewer socially isolated individuals and a lower employee turnover. The program's success in improving leader-subordinate relationships emerges as a likely mechanism to explain these results.
Keywords: C93; M14; M53; 330; workplace climate; relational dynamics; leadership quality; RCT